Antecedents Of Turnover Intention In Al Baik Supermarket Employees - Surya Kusumah; Anoesyirwan Moeins; Marhalinda Marhalinda (International Journal of Economics and Management Research, 2024)
The aim of this research is to analyze the influence of organizational commitment and job satisfaction on turnover intention among Al Baik Supermarket employees. In this research it can be seen that this research method is a quantitative research method. In this research, the sampling method used a saturated sampling technique. The saturated sampling method is a sampling technique when all members of the population are used as samples. Data analysis carried out in this research used SPSS version 21 to process the data where it can be seen that the stages carried out were research instrument testing which consisted of data quality testing, classical assumption testing, multiple regression analysis testing, coefficient of determination testing, and hypothesis testing. Partial test results show that organizational commitment and job satisfaction have a significant effect on turnover intention among supermarket employees. Second, organizational commitment has a negative and significant effect on turnover intention. Third, job satisfaction has a negative and significant effect on turnover intention.